2017
DOI: 10.1017/s0959270916000502
|View full text |Cite
|
Sign up to set email alerts
|

Large changes in the avifauna in an extant hotspot of farmland biodiversity in the Alps

Abstract: SummaryLarge declines of farmland bird species have been observed in the lowlands of Western Europe, whereas important populations of some of these species have survived in parts of Eastern and Southern Europe and in small areas within Western Europe, e.g. in parts of the Alps. However, such extant hotspots of farmland biodiversity are at risk: The economic and technical developments threaten to erode biodiversity in existing hotspots, potentially repeating the collapse previously observed in Western Europe. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…A study in the French Alps showed that this is still true for farmland generalists, but that farmland specialists (which match quite well with our meadow specialists) also declined at elevations higher than 1,000 m (Archaux, ). Coherent patterns had been reported from the Swiss Alps (Korner, Graf, & Jenni, ) and suggest that recent agricultural transformations are also impacting these species in mountain “refuges”, which are rapidly losing their conservation potential for farmland birds.…”
Section: Discussionmentioning
confidence: 84%
“…A study in the French Alps showed that this is still true for farmland generalists, but that farmland specialists (which match quite well with our meadow specialists) also declined at elevations higher than 1,000 m (Archaux, ). Coherent patterns had been reported from the Swiss Alps (Korner, Graf, & Jenni, ) and suggest that recent agricultural transformations are also impacting these species in mountain “refuges”, which are rapidly losing their conservation potential for farmland birds.…”
Section: Discussionmentioning
confidence: 84%
“…Mountain species are among the most threatened ones (Dirnböck et al, 2011), and in particular mountain birds are highly threatened because of both climate change (Brambilla et al, 2018b;Imperio et al, 2013;Lehikoinen et al, 2019;Revermann et al, 2012;Scridel et al, 2018;Sekercioglu et al, 2008) and land-cover change (Chamberlain et al, 2016), and the species inhabiting mountain grassland are particularly at risk (Brambilla et al, 2010;Chamberlain et al, 2013;Korner et al, 2018). The effects of climate and land-cover characteristics, and the impact of the relative changes, often come in the form of intermixed, overlapping effects, with interactions often hard to disentangle (de Chazal and Rounsevell, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Brambilla et al, 2018a). In fact, in a large part of Europe, seminatural grasslands underwent a dramatic decline in recent decades (Pe'er et al, 2014) and, especially in the southern part of the continent, they are often confined to mountain regions (Korner et al, 2018), thus in climates colder than in the adjacent regions. Several species tied to this habitat are now largely restricted to mountains (Assandri et al, 2019a), but this could be linked either to habitat tracking or climate tracking under a changing temperature in these regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from other groups (e.g. birds) suggest that mountain ranges (including the Alps) are no more considerable mountain refugia for lowland species impacted by global change (Archaux, 2007; Korner et al ., 2017; Assandri et al ., 2019b; Fourcade et al ., 2019), and this is likely to be true also for dragonflies. In the last 30 years, the legal protection accorded to all sites investigated probably allowed to slow down species loss, but, based on this study, it is clear that the impacts of human activity on dragonfly communities are much more deeply rooted in time.…”
Section: Discussionmentioning
confidence: 99%